Situation Report: Romania, 18 July 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romanian Changes in Meat Prices, Consumer Goods' Production, and Income President of People's Republic of the Congo in Bucharest Trofin Appointed Chairman of the Committee for Problems of the People's Councils Law on Customs' Duties Published Changes in the Union of Communist Youth Leadership Romania Is Expanding the Political Training of Foreign Trade Union Officials Freedom of Form and Style to Be Restricted? CC Decision on Improving Education